Implicaţiile participării asupra dezvoltării locale. Studiu de caz: Horezu, judeţul Vâlcea - Petrescu, Claudia (Calitatea Vieții, 2009)
The article is rooted in the question: What particularly makes a local development program work? This way, the article analyzes the factors that contribute to the success of local development and the problems that frequently appear in it. Our endeavor is concentrating on the evidentiation of the fundamental role that the participation of all the social actors of the community plays in the implementation of a local development program. Finally, it is presented and debated also the performance of Horezu town within the economic development program that the community engaged in.